Development of a new device to measure finger's mean arterial pressure - Chellathurai, Bumaran (2018)
Measuring the blood pressure is a vital process in order to diagnose the health problem particularly to avoid the heart attack or stroke. Currently, there are two common procedures to test the blood pressure namely via the automated oscillometric device and the manual auscultatory device. Both oscillometric and auscultatory methods are performed on the human arm by using a blood pressure cuff. The above measurement methods are discomfort and time consuming since the cuff is placed on the human arm that involves inflation and deflation process. Hence, a new development of the Finger Mean Arterial Pressure (Finger M.A.P) device is proposed as an alternative measurement device. Instead of placing the cuff on the human arm, a new Finger M.A.P device allows us to measure the blood pressure on the finger. This type of measurement is derived from the photoplethysmography (PPG) signal which conventionally used to estimate the oxygen saturation level. A series of tests based on 10 subjects have been conducted in order to validate the Finger M.A.P device. From statistical analysis using Pearson correlation coefficient, the R value of 0.982 and 0.9416 are obtained when the data of finger’s mean arterial pressure and brachial mean arterial pressure (oscillometric based and korotkoff based respectively) are compared. These results show that the Finger M.A.P device produced sufficient signal characteristic close to the signal produced by the automated oscillometric and the manual auscultatory device. Certainly, these preliminary results show that there is a correlation between a conventional technique (i.e. via automated oscillometric device and the manual auscultatory device) and a newly proposed measurement technique (via Finger M.A.P device).